Effect of severity of hypertension on brain stem auditory evoked potentials - V., Roseline Jesintha; P., Vinupradha P. (International Journal of Research in Medical Sciences, 2018)
Background: Hypertension is one of the most important public health problems among worldwide. Central nervous system dysfunctions are common in these patients due to micro-infarctions caused by arteriolar spasm of cerebral blood vessels. This will lead to hypoperfusion, subcortical white matter demyelination, and cognitive decline. The Brainstem auditory evoked potentials (BAEP) are far field subcortical electrical potentials which provide an objective electrophysiological method for assessing the auditory pathway from auditory nerve to the brainstem. Aim and objective of the study was to assess the effect of increasing severity of hypertension on the brainstem auditory pathway, among the patients of essential hypertension. Methods: A total of 75 subjects of age group 30 to 60 years were included in the study. Among them 25 were healthy age and sex matched controls (Group I), 25 were stage 1 hypertensives (Group IIa) and 25 were stage 2 hypertensives (Group IIb) as per JNC 7 criteria. The absolute latencies I, III, V and interpeak latencies (IPL) I-III, III-V, I-V were recorded by using Neuroperfect EMG 2000 system with installed BAER and data were statistically analyzed using Student unpaired t test. Results: All the hypertensive (Group IIa and IIb) patients were found to have significantly prolonged absolute latency of wave III, V and IPL III-V, I-V as compared to that of normal healthy controls. The wave V latency was prolonged as the severity of hypertension increased. Intergroup comparison among hypertensive patients (Group IIa and IIb) revealed a significant prolongation of absolute latency of Wave III, V and IPL III-V, I-V. Conclusions: The results show that there exists a sensory deficit along with synaptic delay across the auditory pathway in the hypertensive patients and the sensory deficit progresses with the severity of the disease.